Impactos ambientais na microbacia do rio Vacacaí-Mirim em Santa Maria - RS. - Gracioli, Cibele Rosa (2005)
The renewable natural resources sustain the balance between the man and the nature. The destruction of one of those resources represents the unbalance and the man's future destruction. Such resources accomplish a social function to the man's service and of the society. Starting from the moment that the man began to use the renewable natural resources in their multiple forms, the environmental impact was felt by the environment. The breaking in the normal patterns of the natural resources is what one can call environmental impact. Then, the environmental impact is the alteration in the middle or in some of their components for certain action or activity. Those alterations need to be quantified, therefore they present relative variations, could be positive or negative, big or small. The objective of studying the environmental impacts is, mainly, evaluating the consequences of some actions, so that it can have the prevention of the ambient certain quality that can suffer the execution of certain projects or actions, or soon after the implementation of the same ones. This evaluation had been consisted in two stages: the first one, with the analysis of the variables environmental factors and actions proposed by Leopold-Rocha's matrix (2002), and the second one, for the grouping analysis for the WARD method, with the statistical package SAS SYSTEM 8.2. THE degree of medium real deterioration obtained by Leopold-Rocha's matrix had been 29%, showing that the referred place is quite deteriorated, once the acceptable environment deterioration tax is 10%. In the grouping analysis for the WARD method it had been possible the separation of the proposed actions in two different groups (A and B). The A group is constituted by: regime modification; land transformation and constructions; and other, with magnitude (11,63%) and importance (17,64%) average, being the actions group that cause more impact in the micro-basin. It was also possible the separation of groups of environmental factors in three different groups (A, B and C). The C factors group (cultural factors: aesthetic and of human interest) it had been presented the highest average in relation to the magnitude (9,91%) and to the importance (13,86%), denoting to be the environmental factors group that more suffered by the human action. In that aspect, the objective of this work had been consisted of evaluating the micro-basin deterioration degree of Vacacaí-Mirim river, that is in the DNOS dam shore (National Department of Works and Sanity) in Santa Maria, RS, and to recommend reliever and compensatory measures for the recovery of the environment of the place.